The landscape of management and outcome of children with congenitally corrected transposition of the great arteries: a single-center experience - Alahmed, Yazeed Saleh; Jijeh, Abdulraouf M. Z.; Alsaiad, Abdulsalam M.; Yelbuz, T. Mesud; Kabbani, Mohamed S.; Alghamdi, Abdullah A.; Alhabshan, Fahad; Alibrahim, Ibrahim J. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo compare the outcomes in patients with congenitally corrected transposition of the great arteries (ccTGA) who were offered different surgical management strategies.Design and settingsWe retrospectively included all patients from our center diagnosed with ccTGA between 2000 and 2021. The cohort was divided into four groups: (1) patients with systemic right ventricle; (2) patients with anatomic repair (in the form of an atrial and arterial switch or an atrial switch and Rastelli operation); (3) patients with a one-and-a-half ventricle repair (hemi-Mustard type) and bidirectional cavopulmonary connection and placement of a right ventricle to pulmonary artery conduit; and (4) patients with a single ventricle who were not suitable for biventricular repair.ResultsThe study included 42 patients with ccTGA. In 39 patients (93%), ccTGA was associated with other congenital heart defects. Group 1 (systemic right ventricle) comprised 16 patients (38%); seven of them underwent pulmonary artery banding, with a reduction in tricuspid valve regurgitation seen in four patients. Group 2 (anatomic group) and Group 3 (one-and-a-half ventricle group) each had three patients (7%). Group 4 (single-ventricle palliation) consisted of 17 patients (40%); 15 of them (88%) completed total cavopulmonary connection. Three early mortalities (7%) were recorded.ConclusionsPatients who underwent anatomical repair (Rastelli-type) or a one-and-a-half ventricle repair (hemi-Mustard type) showed a good outcome with satisfactory biventricular function. Moreover, single-ventricle palliation showed excellent mid-term results in patients with ccTGA. PA banding may reduce tricuspid regurgitation in patients with ccTGA. A follow-up of our managed patients by an individualized plan demonstrated satisfactory outcomes.